Imitation: Not in Our Genes - Heyes, C (Cell Press, 2016)
A powerful longitudinal study has failed to find any evidence that newborn babies can imitate facial gestures, hand movements or vocalisations. After 40 years of uncertainty, these findings indicate that humans learn to imitate; this capacity is not inborn.